Nano-porous membrane material for reducing Ag / Au / Pt content in electronic-grade sulfuric acid and preparation method of nano-porous membrane material
By preparing PVDF/SGO nanoporous membrane materials, the problem of high content of Ag/Au/Pt heavy metal impurities in electronic-grade sulfuric acid is solved, and the preparation of high-purity sulfuric acid and the long-life use of the membrane materials are achieved.
Patent Information
- Application Number
- CN202411969638.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-30
Smart Images

Figure CN119838574A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic chemical products, and in particular to a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid and a preparation method thereof. Background Art
[0002] Electronic grade sulfuric acid is also known as ultrapure sulfuric acid, high purity sulfuric acid, etc. As a chemical reagent, it is widely used in integrated circuits (IC), semiconductors and other microelectronics industries. In the wafer production process, electronic grade sulfuric acid is mainly responsible for photolithography, cleaning, corrosion, etc. of the wafer, which can effectively remove inorganic residues, impurity particles and carbon deposits on the wafer, thereby ensuring the quality and performance of the wafer. In addition, electronic grade sulfuric acid can also be used as a solution, mostly used in the production of electrolytes for lithium batteries and other rechargeable batteries.
[0003] There are two main methods for preparing electronic grade sulfuric acid: the industrial sulfuric acid distillation method, which uses industrial sulfuric acid as raw material and adds a strong oxidant for distillation, and can produce finished products on a small scale; the sulfur trioxide gas absorption method, which uses ultrapure water to directly absorb clean sulfur trioxide gas to produce finished products, and can be produced on a large scale. Among them, the distillation method has high energy consumption and high cost, and some impurities are difficult to remove. The waste gas and acid mist generated are harmful to the human body and are not conducive to environmental protection. It is only suitable for small-scale production. The sulfur trioxide gas absorption method is to purify sulfur trioxide gas, and then absorb it with ultrapure water or washed sulfuric acid to produce high-purity sulfuric acid. This method can effectively avoid the above-mentioned shortcomings of the distillation method, but the existing gas absorption method cannot effectively remove sulfur dioxide gas, so that the prepared sulfuric acid contains a certain amount of trace sulfur dioxide impurities, which affects the performance of sulfuric acid.
[0004] With the rapid development of my country's integrated circuit, semiconductor and lithium battery markets, the continuous advancement of technology and the continuous improvement of component precision, electronic-grade sulfuric acid plays a vital role in the manufacturing process of integrated circuits, semiconductors and lithium batteries. Especially in the cleaning and etching process of silicon wafers, the presence of heavy metal impurities has a significant impact on the performance of electronic-grade sulfuric acid:
[0005] 1. Affecting the quality and production yield of wafers: In the semiconductor manufacturing process, electronic grade sulfuric acid is mainly used to clean and etch wafers. The presence of Ag ions will form tiny particles or defects on the surface of the wafer, which will affect the quality and production yield of the wafer, resulting in more waste and rework.
[0006] 2. Impact on the diffusion effect of the diffusant: Impurity ions such as Au will affect the diffusion effect of the diffusant
[0007] 3. Reduce etching effect: Pt ions have strong chemical stability and low solubility. Therefore, when Pt ions exist as impurities in electronic-grade sulfuric acid, they may reduce the corrosiveness of sulfuric acid and reduce its etching effect. In addition, the presence of Pt ions in electronic-grade sulfuric acid may affect the activity and solubility of electronic-grade sulfuric acid on metal surfaces.
[0008] 4. Reduce IC yield: During the processing of silicon wafers, insoluble solid particles or metal ions may conduct electricity between fine circuits and cause short circuits. A few metal ions or dust are enough to make ICs with smaller line widths scrapped, resulting in a drop in IC yield of about 50%.
[0009] 5. Photolithography defects and uneven oxide layer: Dust particles can cause photolithography defects and uneven oxide layer, affecting the plate making quality and plasma etching process.
[0010] Therefore, in order to obtain high-quality and high-yield integrated circuit chips, very pure electronic-grade sulfuric acid must be used to clean silicon wafers to remove various contaminants and reduce the impact of heavy metal impurities. This requires the development of an electronic-grade sulfuric acid with extremely low heavy metal content to solve the problem of high content of specific metal ion impurities in the existing electronic-grade sulfuric acid purification, so as to meet the high purity requirements of various industries for electronic-grade sulfuric acid and the sharp increase in the demand for high-purity sulfuric acid. Summary of the invention
[0011] In order to overcome the deficiencies of the prior art, one of the objectives of the present invention is to provide a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid.
[0012] The second object of the present invention is to provide a method for preparing a nanoporous membrane material for reducing the Ag / Au / Pt content in electronic grade sulfuric acid.
[0013] One of the purposes of the present invention is achieved by adopting the following technical scheme: a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid, wherein the nanoporous membrane material uses N-methylpyrrolidone as a solvent, polyvinylidene fluoride as a polymer, glass fiber and graphite powder as additives, and sulfonated graphene oxide as a chemical adsorption complexing agent, and is configured into a membrane liquid with a viscosity suitable for scraping and stable, and the membrane is scraped and coated to obtain a PVDF / SGO nanoporous membrane material.
[0014] Optionally, the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 85-95:5-15, the amount of the glass fiber is 5-20% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, the amount of graphite powder is 5-15% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, and the amount of graphene oxide is 0.5-2% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride.
[0015] Optionally, the mass ratio of carbon, oxygen, sulfur and nitrogen in the sulfonated graphene oxide is 6.2:3.7:0.4:0.5.
[0016] The second object of the present invention is achieved by adopting the following technical solution: A method for preparing a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid, comprising the following steps:
[0017] (1) preparing a basic scraping liquid: weighing 85-95% by mass of N-methylpyrrolidone and 5-15% by mass of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, mixing the above components, stirring for 1-3 hours in a stirrer, and vacuum defoaming for 5-30 minutes to obtain a basic scraping liquid;
[0018] (2) preparing a scraping liquid: weighing 5 to 20% of the total weight of the basic scraping liquid, 5 to 15% of graphite powder, and 0.5 to 2% of sulfonated graphene oxide, and mixing the glass fiber, graphite powder, and sulfonated graphene oxide with the basic scraping liquid obtained in step (1), stirring in a mixer for 1 to 3 hours, and vacuum defoaming for 5 to 30 minutes to obtain a scraping liquid;
[0019] (3) Scraping: pouring the scraping liquid obtained in step (2) into a scraping coater, using the scraping coater to scrape a film with a thickness of 200 to 1000 μm on a quartz plate, and then soaking the film in ultrapure water for 1 to 24 hours to obtain a scraped film;
[0020] (4) Drying: Dry the coated film obtained in step (3) for 1 to 3 hours to obtain a PVDF / SGO nanoporous membrane material.
[0021] Optionally, in step (1), the mass percentage of the N-methylpyrrolidone is 88-92%, the mass percentage of the polyvinylidene fluoride is 8-12%, and the sum of the mass percentages of the two components is 100%.
[0022] Optionally, in step (2), the amount of graphene oxide is 2-4% of the total weight of the basic scraping liquid; the amount of glass fiber is 5-20% of the total weight of the basic scraping liquid, the amount of graphite powder is 5-15% of the total weight of the basic scraping liquid, and the amount of graphene oxide is 0.5-2% of the total weight of the basic scraping liquid.
[0023] Optionally, in step (3), the process parameters of the scraping coater are as follows: the reciprocating scraping speed is 8 to 12 mm / s, and the scraping temperature is at room temperature.
[0024] Optionally, the molecular weight of the polyvinylidene fluoride is 300,000 to 500,000.
[0025] Optionally, the preparation method of the sulfonated graphene oxide is as follows:
[0026] (21) adding graphene oxide to ultrapure water, and ultrasonically dispersing for 50 to 70 minutes to obtain a suspension; the amount ratio of the graphene oxide to the ultrapure water is 0.1 to 1 g: 250 ml;
[0027] (22) adding p-aminobenzenesulfonic acid to the suspension obtained in step (21), stirring under an oil bath condition of 75-85° C., reacting for 5-7 hours, and obtaining an SGO precipitate; the mass ratio of p-aminobenzenesulfonic acid to graphene oxide is 0.2-0.8:1;
[0028] (23) centrifugally filtering the SGO precipitate obtained in step (22) at 4500-5500 rpm, and washing with ultrapure water for multiple times to remove residual p-phenylaminosulfonic acid to obtain a flocculent product;
[0029] (24) The flocculent product is centrifuged at an ultra-high speed of 4500-5500 rpm, the supernatant is removed, and the product is freeze-dried to obtain sulfonated graphene oxide.
[0030] Optionally, in step (21), the graphene oxide is prepared by the following steps:
[0031] (211) At room temperature, graphite powder and sodium nitrate are added to a reactor and a rotor is added; 300 ml of concentrated sulfuric acid is poured in and magnetic stirring is performed; the amount ratio of the graphite powder, sodium nitrate and concentrated sulfuric acid is 3-5 g: 2-3 g: 100 ml;
[0032] (212) Slowly add potassium permanganate into the reactor under an ice bath, cover with plastic wrap, react at room temperature for 4 days, and stir 2 to 3 times a day to release heat; the mass ratio of potassium permanganate to graphite powder is 3 to 5:1;
[0033] (213) After 4 days of reaction, 500–1000 ml of deionized water was slowly added several times, stirred, and heat was released; 50–100 ml of hydrogen peroxide was added, stirred several times, and the reaction formed a golden sand-like graphite oxide dispersion, which was cooled to room temperature;
[0034] (214) The golden sand-like graphite oxide dispersion was centrifuged at 4500-5500 rpm for 5 min, the upper layer was discarded, deionized water was added to disperse the gel-like graphene oxide, and the mixture was stirred and centrifuged at 4500-5500 rpm for a second time. The upper layer was discarded to remove sulfuric acid.
[0035] (215) Deionized water was added, shaken, and ultrasonicated on ice for 3–5 min. Centrifugation was performed for the third time at 1500–2500 rpm for 3–5 min. This step was repeated until the upper layer was no longer viscous. The lower layer was collected and freeze-dried to obtain graphene oxide.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) This application prepares a new type of super adsorption material - PVDF / SGO nanoporous membrane material, which can effectively solve the problem of high content of specific metal ion impurities in the existing high-purity sulfuric acid purification, especially with high removal ability for Ag, Au, and Pt metal ions.
[0038] The PVDF / SGO nanoporous membrane material of the present invention is arranged behind the four-stage distillation tower to increase the adsorption and removal of specific metal ions of electronic-grade sulfuric acid. Its porous structure can not only effectively remove organic macromolecules, bacteria, viruses, anionic impurities and other impurities in electronic-grade sulfuric acid, but also effectively remove Ag, Au, Pt metal ion impurities, thereby meeting the high purity requirements of various industries for electronic-grade sulfuric acid and the sharp increase in the demand for high-purity sulfuric acid.
[0039] (2) The novel super-adsorption material prepared by the present invention, PVDF / SGO nanoporous membrane material, has a reasonable formula design and effectively improves the service life of the membrane material. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a scanning electron microscope (SEM) test image (100 nm) of the PVDF / SGO nanoporous membrane material of the preferred embodiment 2 of the present invention;
[0041] Figure 2 This is a scanning electron microscope (SEM) test image (2 μm) of the PVDF / SGO nanoporous membrane material of the preferred embodiment 2 of the present invention;
[0042] Figure 3 The SEM test image (10 μm) of the sulfonated graphene oxide SGO used in the preferred embodiment 2 of the present invention;
[0043] Figure 4 To obtain Figure 3 The distribution diagram of carbon, oxygen, sulfur and nitrogen elements in the EDS test at ① and ② in the SEM image;
[0044] Figure 5 To obtain Figure 3 The carbon, oxygen, sulfur and nitrogen content in the EDS test at ① in the SEM image;
[0045] Figure 6 To obtain Figure 3The carbon, oxygen, sulfur and nitrogen content in the EDS test at point ② in the SEM image;
[0046] Figure 7 Another SEM and EDS test image (10 μm) of the sulfonated graphene oxide SGO used in the preferred embodiment 2 of the present invention;
[0047] Figure 8 To obtain Figure 7 The distribution diagram of carbon, oxygen, sulfur and nitrogen elements in the EDS test at point ③ in the SEM image;
[0048] Fig. 9 To obtain Figure 7 The carbon, oxygen, sulfur and nitrogen content in the EDS test at point ③ in the SEM image;
[0049] Fig.10 This is a data diagram of the removal of Ag metal ions from high-purity sulfuric acid by the PVDF / SGO nanoporous membrane material of the preferred embodiment 2 of the present invention;
[0050] Fig.11 This is a data diagram of the removal of Au metal ions from high-purity sulfuric acid by the PVDF / SGO nanoporous membrane material of the preferred embodiment 2 of the present invention;
[0051] Fig.12 This is a data chart showing the removal of Pt metal ions from high-purity sulfuric acid by the PVDF / SGO nanoporous membrane material of preferred embodiment 2 of the present invention. DETAILED DESCRIPTION
[0052] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0053] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0054] The invention provides a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid. The nanoporous membrane material uses N-methylpyrrolidone as a solvent, polyvinylidene fluoride as a polymer, glass fiber and graphite powder as additives, and sulfonated graphene oxide as a chemical adsorption complexing agent. The nanoporous membrane material is configured into a membrane liquid with a viscosity suitable for scraping and stable, and the PVDF / SGO nanoporous membrane material is obtained by scraping and coating.
[0055] As a further embodiment, the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 85-95:5-15, the amount of the glass fiber is 5-20% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, the amount of graphite powder is 5-15% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, and the amount of graphene oxide is 0.5-2% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride.
[0056] As a further embodiment, the mass ratio of carbon, oxygen, sulfur and nitrogen in the sulfonated graphene oxide is 6.2:3.7:0.4:0.5.
[0057] The present invention also provides a method for preparing a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid, comprising the following steps:
[0058] (1) preparing a basic scraping liquid: weighing 85-95% by mass of N-methylpyrrolidone and 5-15% by mass of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, mixing the above components, stirring for 1-3 hours in a stirrer, and vacuum defoaming for 5-30 minutes to obtain a basic scraping liquid;
[0059] (2) preparing a scraping liquid: weighing 5 to 20% of the total weight of the basic scraping liquid, 5 to 15% of graphite powder, and 0.5 to 2% of sulfonated graphene oxide, and mixing the glass fiber, graphite powder, and sulfonated graphene oxide with the basic scraping liquid obtained in step (1), stirring in a mixer for 1 to 3 hours, and vacuum defoaming for 5 to 30 minutes to obtain a scraping liquid;
[0060] (3) Scraping: pouring the scraping liquid obtained in step (2) into a scraping coater, using the scraping coater to scrape a film with a thickness of 200 to 1000 μm on a quartz plate, and then soaking the film in ultrapure water for 1 to 24 hours to obtain a scraped film;
[0061] (4) Drying: Dry the coated film obtained in step (3) for 1 to 3 hours to obtain a PVDF / SGO nanoporous membrane material.
[0062] As a further embodiment, in step (1), the mass percentage of the N-methylpyrrolidone is 88-92%, the mass percentage of the polyvinylidene fluoride is 8-12%, and the sum of the mass percentages of the two components is 100%.
[0063] As a further embodiment, in step (2), the amount of graphene oxide is 2-4% of the total weight of the basic scraping liquid; the amount of glass fiber is 5-20% of the total weight of the basic scraping liquid, the amount of graphite powder is 5-15% of the total weight of the basic scraping liquid, and the amount of graphene oxide is 0.5-2% of the total weight of the basic scraping liquid.
[0064] As a further embodiment, in step (3), the process parameters of the scraping coater are as follows: the reciprocating scraping speed is 8 to 12 mm / s, and the scraping temperature is at room temperature.
[0065] As a further embodiment, the molecular weight of the polyvinylidene fluoride is 300,000 to 500,000.
[0066] As a further embodiment, the preparation method of the sulfonated graphene oxide is as follows:
[0067] (21) adding graphene oxide to ultrapure water, and ultrasonically dispersing for 50 to 70 minutes to obtain a suspension; the amount ratio of the graphene oxide to the ultrapure water is 0.1 to 1 g: 250 ml;
[0068] (22) adding p-aminobenzenesulfonic acid to the suspension obtained in step (21), stirring under an oil bath condition of 75-85° C., reacting for 5-7 hours, and obtaining an SGO precipitate; the mass ratio of p-aminobenzenesulfonic acid to graphene oxide is 0.2-0.8:1;
[0069] (23) centrifugally filtering the SGO precipitate obtained in step (22) at 4500-5500 rpm, and washing with ultrapure water for multiple times to remove residual p-phenylaminosulfonic acid to obtain a flocculent product;
[0070] (24) The flocculent product is centrifuged at an ultra-high speed of 4500-5500 rpm, the supernatant is removed, and the product is freeze-dried to obtain sulfonated graphene oxide.
[0071] As a further embodiment, in step (21), the graphene oxide is prepared by the following steps:
[0072] (211) At room temperature, graphite powder and sodium nitrate are added to a reactor and a rotor is added; 300 ml of concentrated sulfuric acid is poured in and magnetic stirring is performed; the amount ratio of the graphite powder, sodium nitrate and concentrated sulfuric acid is 3-5 g: 2-3 g: 100 ml;
[0073] (212) Slowly add potassium permanganate into the reactor under an ice bath, cover with plastic wrap, react at room temperature for 4 days, and stir 2 to 3 times a day to release heat; the mass ratio of potassium permanganate to graphite powder is 3 to 5:1;
[0074] (213) After 4 days of reaction, 500–1000 ml of deionized water was slowly added several times, stirred, and heat was released; 50–100 ml of hydrogen peroxide was added, stirred several times, and the reaction formed a golden sand-like graphite oxide dispersion, which was cooled to room temperature;
[0075] (214) The golden sand-like graphite oxide dispersion was centrifuged at 4500-5500 rpm for 5 min, the upper layer was discarded, deionized water was added to disperse the gel-like graphene oxide, and the mixture was stirred and centrifuged at 4500-5500 rpm for a second time. The upper layer was discarded to remove sulfuric acid.
[0076] (215) Deionized water was added, shaken, and ultrasonicated on ice for 3–5 min. Centrifugation was performed for the third time at 1500–2500 rpm for 3–5 min. This step was repeated until the upper layer was no longer viscous. The lower layer was collected and freeze-dried to obtain graphene oxide.
[0077] The following are specific embodiments of the present invention. Unless otherwise specified, the raw materials, equipment, etc. used in the following embodiments can be obtained by purchase.
[0078] Example 1
[0079] A PVDF / SGO nanoporous membrane material is prepared by the following steps:
[0080] (1) Prepare a basic scraping liquid: Weigh 85% by mass of N-methylpyrrolidone DMF and 15% by mass of polyvinylidene fluoride PVDF, the sum of the mass percentages of the two components being 100%, mix the above components, stir for 1 hour in a blender, and defoam for 5 minutes in a vacuum to obtain a basic scraping liquid; wherein the PVDF is selected from Solef 6010 PVDF of Solvay, USA, and has a molecular weight of 400,000.
[0081] (2) preparing a scraping liquid: weighing 5% of the total weight of the basic scraping liquid, 5% of the graphite powder, and 0.5% of the sulfonated graphene oxide, and mixing the glass fiber, graphite powder, and sulfonated graphene oxide with the basic scraping liquid obtained in step (1), stirring for 1 hour in a stirrer, and vacuum defoaming for 5 minutes to obtain a scraping liquid;
[0082] (3) Scraping: pour the scraping liquid obtained in step (2) into a scraping coater, use the scraping coater to scrape a film with a thickness of 200 μm on a quartz plate, and then soak the film in ultrapure water for 1 hour to obtain a scraped film;
[0083] (4) Drying: The coated film obtained in step (3) was air-dried for 1 h to obtain a PVDF / SGO nanoporous membrane material.
[0084] Example 2
[0085] A PVDF / SGO nanoporous membrane material is prepared by the following steps:
[0086] (1) Prepare a basic scraping liquid: Weigh 90% by mass of N-methylpyrrolidone DMF and 10% by mass of polyvinylidene fluoride PVDF, the sum of the mass percentages of the two components being 100%, mix the above components, stir for 2 h in a mixer, and defoam for 15 min in a vacuum to obtain a basic scraping liquid; wherein the PVDF is selected from Solef 6010 PVDF of Solvay, USA, and has a molecular weight of 400,000.
[0087] (2) preparing a scraping liquid: weighing 15% of the total weight of the basic scraping liquid, glass fiber, 10% of graphite powder, and 1% of sulfonated graphene oxide, and mixing the glass fiber, graphite powder, and sulfonated graphene oxide with the basic scraping liquid obtained in step (1), stirring for 2 h in a stirrer, and vacuum defoaming for 15 min to obtain a scraping liquid;
[0088] (3) Scraping: pour the scraping liquid obtained in step (2) into a scraping coater, use the scraping coater to scrape a film with a thickness of 300 μm on a quartz plate, and then soak the film in ultrapure water for 12 h to obtain a scraped film;
[0089] (4) Drying: The coated film obtained in step (3) was air-dried for 2 h to obtain a PVDF / SGO nanoporous membrane material.
[0090] Example 3
[0091] A PVDF / SGO nanoporous membrane material is prepared by the following steps:
[0092] (1) Prepare a basic scraping liquid: Weigh 95% by mass of N-methylpyrrolidone DMF and 5% by mass of polyvinylidene fluoride PVDF, the sum of the mass percentages of the two components being 100%, mix the above components, stir for 3 hours in a mixer, and defoam for 30 minutes in a vacuum to obtain a basic scraping liquid; wherein the PVDF is selected from Solef 6010 PVDF of Solvay, USA, and has a molecular weight of 400,000.
[0093] (2) preparing a scraping liquid: weighing 20% of the total weight of the basic scraping liquid, glass fiber, 15% of graphite powder, and 2% of sulfonated graphene oxide, and mixing the glass fiber, graphite powder, and sulfonated graphene oxide with the basic scraping liquid obtained in step (1), stirring for 3 hours in a stirrer, and vacuum defoaming for 30 minutes to obtain a scraping liquid;
[0094] (3) Scraping: pour the scraping liquid obtained in step (2) into a scraping coater, use the scraping coater to scrape a film with a thickness of 1000 μm on a quartz plate, and then soak the film in ultrapure water for 24 hours to obtain a scraped film;
[0095] (4) Drying: The coated film obtained in step (3) was air-dried for 3 h to obtain a PVDF / SGO nanoporous membrane material.
[0096] The sulfonated graphene oxide SGO of Examples 1-3 is prepared by the following steps:
[0097] (21) Add graphene oxide GO to ultrapure water and disperse it ultrasonically for 60 minutes to obtain a suspension; the amount ratio of graphene oxide to ultrapure water is 0.5g:250ml; in step (21), the graphene oxide GO is prepared by the following steps: (211) At room temperature, add 10g of graphite powder and 7.5g of sodium nitrate to a reactor and add a rotor; pour in 300ml of concentrated sulfuric acid and stir magnetically; (212) Slowly add 40g of potassium permanganate to the reactor under an ice bath, cover with plastic wrap, react at room temperature for 4 days, and stir 2-3 times a day to release heat; (213) After 4 days of reaction, slowly and repeatedly add 800ml of deionized water, stir, and release heat; Add 60 ml of hydrogen peroxide and stir for several times to react to form a golden sand-like graphite oxide dispersion, which is then cooled to room temperature; (214) centrifuge the golden sand-like graphite oxide dispersion at 5000 rpm for the first time for 5 min, discard the upper layer after centrifugation, add deionized water to disperse the gel-like graphene oxide, stir, centrifuge for the second time at 5000 rpm, discard the upper layer after centrifugation to remove sulfuric acid; (215) add deionized water, shake well, ultrasonicate in an ice bath for 5 min, centrifuge for the third time at 2000 rpm for 5 min, repeat this step until the upper layer is no longer viscous, collect the lower layer, and freeze-dry the lower layer to obtain graphene oxide GO.
[0098] (22) Add 0.2 g of aminobenzenesulfonic acid to the suspension obtained in step (21), stir in an oil bath at 80 °C, and react for 6 h to obtain an SGO precipitate;
[0099] (23) centrifugally filtering the SGO precipitate obtained in step (22) at 5000 rpm, and washing with ultrapure water for multiple times to remove residual p-phenylaminosulfonic acid to obtain a flocculent product;
[0100] (24) The flocculent product was centrifuged at an ultra-high speed of 5000 rpm, and the supernatant was removed after centrifugation. After freeze-drying, sulfonated graphene oxide was obtained.
[0101] Comparative Example 1
[0102] Compared with Example 2, the difference of Comparative Example 1 is that the concentration of the basic scraping liquid in step (1) is too high. Specifically, in step (1), 82% by weight of DMF and 18% by weight of PVDF are weighed and mixed to prepare the basic scraping liquid; the other conditions are the same as those in Example 2.
[0103] Comparative Example 2
[0104] Compared with Example 2, the difference of Comparative Example 2 is that: the concentration of the basic scraping liquid in step (1) is too low. Specifically, in step (1), 96% by weight of DMF and 4% by weight of PVDF are weighed and mixed to prepare the basic scraping liquid; the other conditions are the same as those in Example 2.
[0105] Comparative Example 3
[0106] Compared with Example 2, the difference of Comparative Example 3 is that the polyvinylidene fluoride PVDF in step (1) is selected from PVDF of model number Solef1015 produced by Solvay, USA, with a molecular weight of 1 million, and the other conditions are the same as those of Example 2.
[0107] Comparative Example 4
[0108] Compared with Example 2, the difference of Comparative Example 4 is that no glass fiber is added in step (2), and the other conditions are the same as those of Example 2.
[0109] Comparative Example 5
[0110] Compared with Example 2, the difference of Comparative Example 5 is that no graphite powder is added in step (2), and the other conditions are the same as those of Example 2.
[0111] Comparative Example 6
[0112] Compared with Example 2, the difference of Comparative Example 6 is that the sulfonated graphene oxide SGO used in step (2) is purchased from the sulfonated graphene oxide model 045697616 on the exploration platform, and the other conditions are the same as those in Example 2.
[0113] Comparative Example 7
[0114] Compared with Example 2, the difference of Comparative Example 7 is that the sulfonated graphene oxide SGO used in step (2) is replaced by graphene oxide GO, and the other conditions are the same as those of Example 2. Wherein, the graphene oxide GO is prepared by the following steps: (211) At room temperature, 10 g of graphite powder and 7.5 g of sodium nitrate are added to a reactor, and a rotor is added; 300 ml of concentrated sulfuric acid is poured in and magnetically stirred; (212) 40 g of potassium permanganate is slowly added to the reactor under an ice bath, covered with plastic wrap, and reacted at room temperature for 4 days, stirring 2-3 times a day to release heat; (213) After reacting for 4 days, 800 ml of deionized water is slowly and repeatedly added, stirred, and released heat; 60 ml of hydrogen peroxide is added, stirred several times, and the reaction is a golden sand-like graphite oxide dispersion, which is cooled to room temperature; (214) The golden sand-like graphite oxide dispersion was centrifuged at 5000 rpm for 5 min, the upper layer was discarded, deionized water was added to disperse the gel-like graphene oxide, and the mixture was stirred and centrifuged at 5000 rpm for a second time. The upper layer was discarded to remove sulfuric acid. (215) Deionized water was added, shaken, ultrasonicated in an ice bath for 5 min, and centrifuged at 2000 rpm for a third time for 5 min. This step was repeated until the upper layer was no longer viscous, the lower layer was collected, and the lower layer was freeze-dried to obtain graphene oxide GO.
[0115] Comparative Example 8
[0116] Compared with Example 2, the difference of Comparative Example 8 is that in step (2) of the method for preparing sulfonated graphene oxide SGO, the mass ratio of p-aminobenzenesulfonic acid to graphene oxide is different. Specifically, the mass ratio of p-aminobenzenesulfonic acid to graphene oxide is 0.1:1, and the other conditions are the same as those in Example 2.
[0117] Comparative Example 9
[0118] Compared with Example 2, the difference of Comparative Example 9 is that in step (2) of the method for preparing sulfonated graphene oxide SGO, the mass ratio of p-aminobenzenesulfonic acid to graphene oxide is different. Specifically, the mass ratio of p-aminobenzenesulfonic acid to graphene oxide is 0.9:1, and the other conditions are the same as those in Example 2.
[0119] Effect evaluation and performance testing
[0120] The nanoporous membranes of Examples 1-3 and various comparative examples were tested for their ability to remove specific metal ions, service life and other properties. See Table 1 for the test items and results.
[0121] 1. Cross-flow filtration experiment
[0122] The nanoporous membranes prepared in Examples 1-3 and various comparative examples were tested using a cross-flow filtration integrated device. The membrane is assembled into a cross-flow filtration integrated device, and then the same batch of electronic-grade sulfuric acid is introduced into the liquid inlet. During cross-flow filtration, the flow of electronic-grade sulfuric acid generates two forces on the membrane surface. One is the normal force perpendicular to the membrane surface, which allows the electronic-grade sulfuric acid to pass through the membrane surface, and the other is the tangential force parallel to the membrane surface, which washes away the retained substances (including metal ions) on the membrane surface. Each time the electronic-grade sulfuric acid is filtered for 3 minutes, 1 ml of electronic-grade sulfuric acid is intercepted at the tail end of the liquid outlet; the experiment is repeated 7 times to obtain 7 electronic-grade sulfuric acid filtrates.
[0123] 2. ICP-MS experiment
[0124] The ICP-MS equipment in the Class 100 clean room was used to test the trace amount of metal ions on the sulfuric acid stock solution and the electronic grade sulfuric acid filtrate, that is, the metal ion trace amount of the samples numbered (1) high purity sulfuric acid stock solution, (2) 1st sulfuric acid filtrate, (3) 2nd sulfuric acid filtrate, (4) 3rd sulfuric acid filtrate, (5) 4th sulfuric acid filtrate, (6) 5th sulfuric acid filtrate, (7) 6th sulfuric acid filtrate, and (8) 7th sulfuric acid filtrate was tested. ① ICP-MS is the full name of Inductively Coupled Plasma-Mass Spectrometry. ICP acts as an ion source. ICP uses a high-frequency radio frequency signal applied to an inductor coil to form a high-temperature plasma inside the coil, and through the promotion of gas, the balance and continuous ionization of the plasma are guaranteed. The sample to be analyzed is sent into the atomizer by a peristaltic pump to form an aerosol, which is carried into the center of the plasma torch by the carrier gas to evaporate, decompose, excite and ionize. High-temperature plasma ionizes most elements in the sample to produce an electron and form monovalent positive ions. ② The ions in the plasma are effectively transmitted to the mass spectrometer through the ICP-MS interface; ③ The mass spectrometer is a mass screening and analyzer that detects the intensity of a certain ion by selecting ions with different mass-to-nuclear ratios (m / z) to pass through, and then analyzes and calculates the trace amount of a certain element. The test results select the trace changes of specific metal ions to explain the filtering effect of this membrane material on specific metal ions.
[0125] Table 1 shows the removal and filtration test results of specific metal ions of nanoporous membrane materials in various embodiments
[0126]
[0127] Table 2 Figure 4 , 7 The carbon, oxygen, sulfur and nitrogen mass ratio test results of sulfonated graphene oxide SGO in three locations in the SEM image shown
[0128] Wt% ① ② 3 Carbon Atom 61.0 62.7 61.2 Oxygen Atom 37.9 36.3 38.1 Sulfur Atom 0.3 0.4 0.4 Nitrogen Atom 0.8 0.5 0.3
[0129] Figure 1-2This is a SEM test image of the PVDF / SGO nanoporous membrane material of the preferred embodiment 2 of the present invention, as shown Figure 1-2 As shown, the PVDF / SGO nanoporous membrane prepared by the present invention has uniform surface and internal pore distribution, with a surface pore diameter of 50 to 100 nm and an internal pore diameter of about 100 nm.
[0130] Figure 3-9 The SEM and EDS test images of the sulfonated graphene oxide SGO prepared by the present invention are shown in the figure. As shown in the figure, the sulfonated graphene oxide SGO prepared by the present invention is in the form of flakes, the thickness of a single layer of sulfonated graphene oxide is about 0.8-1.2nm, and the average radial size is 40-60μm. The mass ratio of C, O, S, and N in the sulfonated graphene oxide SGO prepared by this patent is approximately 6.2:3.7:0.4:0.5.
[0131] As shown in the table above and Figure 10-12 As shown, by preparing a new type of super adsorption material - PVDF / SGO nanoporous membrane material, it is possible to effectively reduce the content of specific metal ions of Ag, Au, and Pt in electronic-grade sulfuric acid, and effectively solve the problem of high content of specific metal ion impurities in the existing high-purity sulfuric acid purification.
[0132] In addition, in Comparative Examples 1-2, since the concentration of the basic scraping liquid is too high or too low, the film cannot be formed, and thus the trace amount of metal ions cannot be filtered.
[0133] In Comparative Example 3, the PVDF with a molecular weight of 1 million has a poor film-forming effect, with less SGO on the membrane, and the filtration effect is not as good as the membrane material prepared in the present invention.
[0134] In Comparative Example 4-5, since glass fiber and graphite powder additives were not added during the membrane preparation process, the membrane could not be formed, could not filter trace amounts of metal ions, and could not test the filtration capacity of the membrane.
[0135] Comparative Example 6 uses purchased SGO. Since the SGO has more impurities, more metal ion impurities are introduced during the filtration process, so the percentage exceeds 100%.
[0136] Comparative Example 7 uses homemade graphene oxide GO instead of sulfonated graphene oxide SGO. The higher the degree of sulfonation of GO, the better its adsorption effect.
[0137] In the mass ratio of p-aminobenzenesulfonic acid to GO, the p-aminobenzenesulfonic acid content of Comparative Example 8 is too low, and the degree of GO sulfonation is low, which reduces the filtering effect. The p-aminobenzenesulfonic acid content of Comparative Example 9 is too high, and the degree of GO sulfonation reaches the threshold, which cannot continue to improve the adsorption effect, but instead introduces more impurities.
[0138] 3. Film material service life test
[0139] In the cross-flow filtration experiment, the membrane materials of each example were continuously used to filter and purify sulfuric acid. After 50 filtrations, the membrane materials were taken out and the damage of the membrane materials was observed. The results showed that the nanoporous membrane material prepared by the present invention was not damaged after 50 filtrations under a microscope.
[0140] In summary, the new super-adsorbent material prepared by the present invention, PVDF / SGO nanoporous membrane material, not only effectively solves the problem of high content of specific metal ion impurities in the existing high-purity sulfuric acid purification, but also has a reasonable formula design and effectively improves the service life of the membrane material.
[0141] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid, characterized in that: The nanoporous membrane material uses N-methylpyrrolidone as a solvent, polyvinylidene fluoride as a polymer, glass fiber and graphite powder as additives, and sulfonated graphene oxide as a chemical adsorption complexing agent. It is configured into a membrane liquid with a viscosity suitable for scraping and stability, and the PVDF / SGO nanoporous membrane material is obtained by scraping and coating.
2. The nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid according to claim 1, characterized in that: The mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 85-95:5-15, the amount of the glass fiber is 5-20% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, the amount of graphite powder is 5-15% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, and the amount of graphene oxide is 0.5-2% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride.
3. The nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid according to claim 1, characterized in that: The mass ratio of carbon, oxygen, sulfur and nitrogen in the sulfonated graphene oxide is 6.2:3.7:0.4:0.
5.
4. A method for preparing a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid, characterized in that: The following steps are involved: (1) preparing a basic scraping liquid: weighing 85-95% by mass of N-methylpyrrolidone and 5-15% by mass of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, mixing the above components, stirring for 1-3 hours in a stirrer, and vacuum defoaming for 5-30 minutes to obtain a basic scraping liquid; (2) preparing a scraping liquid: weighing 5 to 20% of the total weight of the basic scraping liquid, 5 to 15% of graphite powder, and 0.5 to 2% of sulfonated graphene oxide, and mixing the glass fiber, graphite powder, and sulfonated graphene oxide with the basic scraping liquid obtained in step (1), stirring in a mixer for 1 to 3 hours, and vacuum defoaming for 5 to 30 minutes to obtain a scraping liquid; (3) Scraping: pouring the scraping liquid obtained in step (2) into a scraping coater, using the scraping coater to scrape a film with a thickness of 200 to 1000 μm on a quartz plate, and then soaking the film in ultrapure water for 1 to 24 hours to obtain a scraped film; (4) Drying: Dry the coated film obtained in step (3) for 1 to 3 hours to obtain a PVDF / SGO nanoporous membrane material.
5. The method for preparing a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid according to claim 4, characterized in that: In step (1), the mass percentage of the N-methylpyrrolidone is 88-92%, the mass percentage of the polyvinylidene fluoride is 8-12%, and the sum of the mass percentages of the two components is 100%.
6. The method for preparing a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid according to claim 4, characterized in that: In step (2), the amount of graphene oxide is 2-4% of the total weight of the basic scraping liquid; the amount of glass fiber is 5-20% of the total weight of the basic scraping liquid, the amount of graphite powder is 5-15% of the total weight of the basic scraping liquid, and the amount of graphene oxide is 0.5-2% of the total weight of the basic scraping liquid.
7. The method for preparing a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid according to claim 4, characterized in that: In step (3), the process parameters of the scraping coater are as follows: the reciprocating scraping speed is 8 to 12 mm / s, and the scraping temperature is at room temperature.
8. The method for preparing a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid according to claim 4, characterized in that: The molecular weight of the polyvinylidene fluoride is 300,000 to 500,000.
9. The method for preparing a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid according to claim 4, characterized in that: The preparation method of the sulfonated graphene oxide is as follows: (21) adding graphene oxide to ultrapure water, and ultrasonically dispersing for 50 to 70 minutes to obtain a suspension; the amount ratio of the graphene oxide to the ultrapure water is 0.1 to 1 g: 250 ml; (22) adding p-aminobenzenesulfonic acid to the suspension obtained in step (21), stirring under an oil bath condition of 75-85° C., reacting for 5-7 hours, and obtaining an SGO precipitate; the mass ratio of p-aminobenzenesulfonic acid to graphene oxide is 0.2-0.8:1; (23) centrifugally filtering the SGO precipitate obtained in step (22) at 4500-5500 rpm, and washing with ultrapure water for multiple times to remove residual p-phenylaminosulfonic acid to obtain a flocculent product; (24) The flocculent product is centrifuged at an ultra-high speed of 4500-5500 rpm, the supernatant is removed, and the product is freeze-dried to obtain sulfonated graphene oxide.
10. The method for preparing a nanoporous membrane material for reducing the content of Ag / Au / Pt in electronic grade sulfuric acid according to claim 9, characterized in that: In step (21), the graphene oxide is prepared by the following steps: (211) At room temperature, graphite powder and sodium nitrate are added to a reactor and a rotor is added; 300 ml of concentrated sulfuric acid is poured in and magnetic stirring is performed; the amount ratio of the graphite powder, sodium nitrate and concentrated sulfuric acid is 3-5 g: 2-3 g: 100 ml; (212) Slowly add potassium permanganate into the reactor under an ice bath, cover with plastic wrap, react at room temperature for 4 days, and stir 2 to 3 times a day to release heat; the mass ratio of potassium permanganate to graphite powder is 3 to 5:1; (213) After 4 days of reaction, 500–1000 ml of deionized water was slowly added several times, stirred, and heat was released; 50–100 ml of hydrogen peroxide was added, stirred several times, and the reaction formed a golden sand-like graphite oxide dispersion, which was cooled to room temperature; (214) The golden sand-like graphite oxide dispersion was centrifuged at 4500-5500 rpm for 5 min, the upper layer was discarded, deionized water was added to disperse the gel-like graphene oxide, and the mixture was stirred and centrifuged at 4500-5500 rpm for a second time. The upper layer was discarded to remove sulfuric acid. (215) Deionized water was added, shaken, and ultrasonicated on ice for 3–5 min. Centrifugation was performed for the third time at 1500–2500 rpm for 3–5 min. This step was repeated until the upper layer was no longer viscous. The lower layer was collected and freeze-dried to obtain graphene oxide.
Citation Information
Patent Citations
Preparation method for composite material of sulfonated graphene / polypyrrole
CN102702520A
Preparing method of superfine manganese carbonate
CN110316760A
Preparation method of graphene oxide-polyethylene glycol / polyvinylidene fluoride composite ultrafiltration membrane
CN111437725A
PMIA mixed matrix ultrafiltration membrane with high flux and anti-pollution performance and preparation and application
CN112755821A
Preparation method and application of sulfonated graphene quantum dot functionalized two-dimensional layered film
CN115779702A